PERSPEKTIF MASYARAKAT, PELAJAR, DAN ATLET MENGENAI PENTINGNYA PEREGANGAN - Azfa Priatna, Kiki Alghifari; Hidayat, Faqih; Fatonah, Nasywa Nurul; Syabani, Muhammad Akmal; Zulfiqor, Zidan Muhammad; Fu’adin, Ahmad (Jendela Inovasi Daerah, 2023)
This research contains various perspectives from participants regarding the importance of stretching before exercising. The purpose of this study was to find out how important stretching was for the participants and what the participants experienced when exercising without stretching. This study uses a Quantitative Research Method (Survey Method) in the form of a Google Form/questionnaire which is distributed via social media (Whatsapp, Instagram or other social media). The people, students and athletes who were the objects of this study came from different sports backgrounds and the age range of the participants was from 16-35 years. The majority of participants with a proportion of 95.2% thought that stretching was very important. But even though it was considered very important, not a few of the participants rarely or even did not stretch before exercising. As a result, minor to severe injuries could not be avoided by the participants. In addition to injuries, the participants who didn't stretch also felt discomfort during exercise, ranging from easy muscle fatigue, easy to experience pain, stiff muscles, increased heart rate and irregular breathing. the majority of participants stretch within 5-10 minutes.